Green HPTLC-method to estimate trans-Cinnamaldehyde in Ayurvedic formulation Sitopaladi Churna - Arun K. S. Parihar; Umakant Sahu; K. S. Karbhal; S. R. Inchulkar; Prashant Kumar Gupta; Arun Kumar Mahapatra; N. S. Chauhan (World Scientific Publishing, 2023)
Traditional medicine is a preferred home remedy for common cold, cough, allergic conditions, etc. in South East Asia. Ayurveda, originated in India, has a long history of treating upper respiratory disorders. Sitopaladi churn (powder) is one of the most sold "over-the-counter" herbal medicine for upper respiratory ailments cure. Quality control and validation is a hindrance for Ayurvedic product development. This study was conducted to estimate and validate for quantitative study of trans-Cinnamaldehyde in Ayurvedic medicine Sitopaladi Churna (SPC) through high-performance thin-layer chromatography (HPTLC) method. The quantitative study was performed at the wavelength 294[Formula: see text]nm and validated as per ICH guidelines. The content of trans-Cinnamaldehyde in SPC was found to be 0.093%. Green HPTLC method is simple and sensitive for standardization and is validated for trans-Cinnamaldehyde in Sitopaladi powder. This method would add a different approach for quality control and assay of SPC.